EXPLORING THE IMPACT OF INFLUENCER AUTHENTICITY ON BRAND PERCEPTION AND CONSUMER TRUST - Dedi Suharyadi; Isroni Isroni; Sukmono Bayu Adhi; Roy Irawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study explores the impact of influencer authenticity on brand perception and consumer trust, with consumer engagement as a mediating variable, specifically focusing on Wardah consumers in Padang. Using a quantitative approach, data was collected from 100 respondents aged 20-30 years who use Wardah products, applying a simple random sampling technique. Structural Equation Modeling (SEM) with Smart PLS was used to analyze relationships among variables. The findings indicate that influencer authenticity has a significant and direct impact on both brand perception and consumer trust, with higher levels of authenticity enhancing consumer perceptions and trust in the brand. Although consumer engagement partially mediates the relationship between influencer authenticity and brand perception, it has a weaker mediating effect on consumer trust. This suggests that while consumer engagement reinforces brand perception, trust in the brand primarily stems from perceptions of influencer authenticity. The results underscore the importance of genuine influencer partnerships for brands like Wardah to foster strong, trust-based connections with their audience, especially in culturally specific markets. This research contributes to a deeper understanding of how influencer marketing dynamics affect consumer attitudes, offering practical implications for brand positioning and trust-building strategies.